Answer:
Option C. [tex]y = (x-8) ^ 2[/tex]
Step-by-step explanation:
If we have a parent function f(x) and we want to make a transformation that translates the graph of f(x) horizontally then we do
[tex]y = f (x + h)[/tex]
Where h is a constant such that:
If [tex]h> 0[/tex] then the graph of f(x) moves h units to the left
If [tex]h <0[/tex] then the graph of f(x) moves h units to the right.
In this case we have the function [tex]y = x ^ 2[/tex] and we know that 8 units are moved to the right. If you move 8 units to the right This means that
[tex]h <0[/tex] and [tex]h = -8[/tex]
So if [tex]f(x) = x ^ 2[/tex] the transformed function will be:
[tex]y = f(x -8)[/tex]
[tex]y = (x-8) ^ 2[/tex]